An integrated evaluation of strategies for enhancing productivity and profitability of resource-constrained smallholder farms in Zimbabwe - Zingore, Shamie; González Estrada, E.; Delve, Robert J.; Herrero, Mario; Dimes, John P.; Giller, Kenneth E. (Elsevier, 2009)
In African smallholder agriculture, improved farm-scale understanding of the interaction between the household, crops, soils and livestock is required to develop appropriate strategies for improving productivity. A combination of models was used to analyse land use and labour allocation strategies for optimizing income for wealthy (2.5 ha with eight cattle) and poor (0.9 ha without cattle) farms in Murewa, Zimbabwe. Trade-offs between profitability, labour use and partial nutrient balances were also evaluated for alternative resource management strategies. Farm data were captured using the Integrated Modelling Platform for Mixed Animal-Crop Systems (IMPACT), which was directly linked to the Household Resource use Optimization Model (HROM). HROM was applied to optimize net cash income within the constraints specific to the households. Effects of alternative nutrient resource management strategies in crop and milk production were simulated using the Agricultural Production Systems Simulator (APSIM) and RUMINANT models, respectively, and the output evaluated using HROM. The poor farm had a net income of US$ 1 yr−1 and the farmer relied on selling unskilled labour to supplement her income. The poor farm’s income was marginally increased by US$18 yr−1 and the soil nitrogen (N) balance was increased from 6 to 9 kg ha−1 yr−1 by expanding groundnut production from the previous 5–25% of the land area. Further increases in area allocated to groundnut production were constrained by lack of labour. On the poor farm, maize production was most profitable when cultivated on a reduced land area with optimal weeding. The wealthy farm had a maize-dominated cropping system that yielded a net cash balance of US$290 yr−1, mainly from the sale of crop produce. Net income could be increased to US$1175 yr−1, by re-allocating the 240 hired labour-days more efficiently, although this reallocation substantially reduced partial soil N and phosphorus (P) balances by 74 kg N ha−1 and 11 kg P ha−1, respectively, resulting in negative nutrient balances. Few opportunities existed to increase productivity and income of the smallholder farms without inducing negative nutrient balances. On the wealthy farm, groundnut was the least profitable crop; shifting its production to the most fertile field did not improve income unless the groundnut residues were fed to lactating cows. The analysis carried out in this paper highlights the need to develop practical technological recommendations and development interventions that consider farm resource endowment (land, fertilizers, manure and labour), variability in soil fertility within farms and competing resource use options.